KORELASI DETERMINAN SOSIAL EKONOMI PETANI DENGAN KECENDERUNGANNYA MERAMBAH HUTAN LlNDUNG D1 TAMAN NASIONAL KERINCI SEBLAT (TNKS) - Purwoko, Agus (Jurnal AGRISEP, 2004)
This research  was  to  analyze  the  relationship    between  determinants  of socio-economics  and farmers' tendency   to clear away the forest in Taman Nasional Kerinci Seblat (TNKS). A survey method was carried out at nine villages in the border of TNKS, Lebong Se/atan subdistrict, Rejang Lebong district.   The total of respondents  were  130 farmers that selected   by proportional simple random sampling based on the size of subpopulation from each village.  Rank Spearman correlation was used to examine the relationship  between determinants   of  socio-economics and  farmers'  tendency  to clear  away  the forest in  TNKS.   The results showed most of farmers tend to dear  away the forest in TNKS.  The variables of socioeconomics related to farmers' tendency were the size of farmland, the financing offann,  and family income.